Keterbukaan Informasi Dalam Pemberitaan Media Elektronik Kaitannya Dengan Penegakan Hukum Pidana Terhadap Asas Praduga Tidak Bersalah - Christian Sipayung, Ronald Fredy (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Presumption of innocence is a universal principle that exists and applies to every country in the world that calls itself a country based on law. In criminal justice theory, there are two criminal justice models, namely: Crime Control Model (CCM) and Due Process Model (DPM). The guarantee for human rights protection cannot only be provided through the inclusion of this principle because the presumption of innocence is 'abstract', so it requires further implementation in the administration of criminal justice. Differences in perspective among law enforcers, especially prosecutors and judges, as well as among the public, result in differences in punishment and charges in one case with another. In addition, the public's understanding differs regarding the principle of the presumption of innocence, resulting in public distrust of the law, which has led to excessive reporting on criminal offences, even though it is not certain that the suspect or defendant actually committed the alleged crime. Key words: disclosure, information presumption of innocence